Analisis Strategi Brand Activation Pertamina International Shipping Oleh Detikcom - Joelio, Marceline; Wijayanti, Ani; Natalia B., Rebecca Milka (Kajian Branding Indonesia, 2024)
This research aims to analyze the Pertamina International Shipping (PIS) brand activation booth strategy used by Detikcom at the Pertamina Eco Run-Fest 2023 event to activate the Pertamina International Shipping message. This research uses qualitative methods that focus on case studies and uses observation, interview and literature study data collection techniques. After the data was collected and triangulated, the results showed that Detikcom used an integrated brand activation strategy with a combination of the One Piece and PIS CSR themes, namely "SEAnergi for the sea". This strategy is carried out by using activation activities that accommodate the entire target audience, namely families, such as ball baths, bracelet making and gold search games. Detikcom's brand activation strategy has proven to be effective in attracting visitor attention and increasing Pertamina International Shipping's brand awareness